Occupational health and workplace monitoring at chemical agent disposal facilities (National Academy Press, 2001)
The United States has maintained a stockpile of chemical warfare agents and munitions for more than half a century. In 1985, Public Law 99-145 mandated an expedited effort to dispose of M55 rockets containing unitary chemical warfare agents because of their potential for self-ignition. This program soon expanded to become the Army Chemical Stockpile Disposal Program (CSDP), with the mission of eliminating the entire stockpile of unitary chemical agents and munitions. The Army developed the baseline incineration system for that purpose. Since 1987, the National Research Council, through the Committee on Review and Evaluation of the Army Chemical Stockpile Disposal Program (Stockpile Committee), has provided technical and scientific advice and counsel to the Army's disposal program and has endorsed the baseline incineration system as an adequate technology for destroying the stockpile. In 1992, after setting several intermediate goals and dates, Congress enacted Public Law 102- 484, which directed the Army to dispose of the entire stockpile by December 31, 2004, a deadline that was changed to April 29, 2007, after the United States ratified the Chemical Weapons Convention.